Application of Proximal Lateral Leg Perforator Flaps for Head and Neck Reconstructions. (November 2014) - Hsu, Honda; Chen, Peir-Rong; Chien, Sou-Hsin; Lee, Jiunn-Tat
Objective: Analyze the reliability, complications, and donor site morbidity of the proximal lateral leg flap when applied to head and neck reconstruction. Study Design: Case series and chart review. Setting: Tertiary care teaching hospital. Subjects and Methods: Nineteen patients who underwent reconstruction of various head and neck defects with this flap were analyzed. The patient demographics, flap characteristics, method of donor site closure, scars of the donor area, complication rates, as well as functional results at the recipient site were assessed. Results: The flap size ranged from 4 × 4 cm to 11 × 8 cm. Vascular pedicle length ranged from 5 to 9 cm. The mean distance of the perforator from the fibula head was 9.2 cm. The mean thickness of this flap was 5.5 mm. All the donor wounds were closed primarily. The flap survival rate was 100%. Conclusion: This flap has the advantages of thinness, short harvesting time, minimal donor site morbidity, and primary closure at the donor site when the flap width is less than 6 cm. This flap may be useful for reconstruction in selected patients with small and thin heads and neck defects.